Retracción por secado en elementos estructurales en una vivienda tipo ubicada en el sector urbano de La Troncal - Amay Lozada, Oswaldo Israel (2019)
The drying retraction refers to a series of deformations of non-instantaneous character, which depend directly on the time, where the gradient of the moisture between the material and the medium in which a concrete structure is immersed or the application of Stress that over-passes the estimated tends to affect the irreversible changes in the structural elements of a construction. Before that, the present study aims to determine the parameters that influence the behavior of the structural elements of a dwelling type, due to the retraction of concrete, in the urban sector of the trunk. The lifting of the information was based on the use of an exploratory research model of experimental character due to the samples requested for the test of the retraction by drying in the dwellings located in the will of God enclosure of that Canton. For the experimental part, the study determined the construction of three reinforced concrete porches, which would provide information on the process of retraction by drying the materials……..